Evidence for the early onset of aberrant promoter methylation in urothelial carcinoma. - Dhawan, D; Hamdy, F; Rehman, I; Patterson, J; Cross, S; Feeley, K; Stephenson, Y; Meuth, M; Catto, J (2006)
There is evidence that carcinoma in situ (CIS) is the precursor of invasive urothelial carcinoma, a tumour characterized by frequent gene promoter methylation. The timing of altered DNA methylation is unknown in this pathway. Here we investigate gene methylation in 196 consecutive samples of normal urothelium, CIS, and tumours from 104 patients with both CIS and invasive urothelial carcinoma using quantitative methyl-sensitive polymerase chain reaction for six genes (p16, p14, E-cadherin, RARbeta2, RASSF1a, and GSTP1). Control normal urothelial samples from 15 patients with no history of urothelial carcinoma were also analysed. Immunohistochemistry established the expression of well-characterized CIS markers p53 and cytokeratin 20. Promoter methylation occurred frequently in both normal urothelium and CIS samples from patients with urothelial carcinoma, and increased with progression from normal to invasive urothelial carcinoma, at both specific loci (chi2 test: E-cadherin, p=0.0001; RASSF1a, p=0.003, RARbeta2, p=0.007, p16, p=0.024) and in general (methylation indices [t-test, p<0.0001]). Methylation was associated with cytokeratin 20 expression (t-test, p=0.004) and poor prognosis, and with increased progression to tumour death in patients whose CIS samples showed methylation, in comparison with those without methylation (log rank p<0.03). Promoter methylation occurs early in the urothelial carcinogenic pathway and appears to be a good biomarker of the invasive urothelial carcinoma phenotype.